2023
DOI: 10.3390/ani13121950
|View full text |Cite
|
Sign up to set email alerts
|

Elements in Soft Tissues of the Young Mediterranean Mussel Mytilus galloprovincialis Lam. 1819 Collected in Sevastopol Bay (Crimea, Black Sea): Effects of Age, Sex, Location, and Principal Morphometric Parameters

Abstract: Although the mussel Mytilus galloprovincialis has been known for decades as an excellent bioindicator of trace element pollution in the marine environment, there is still no information on the effects of a suite of its principal morphometric parameters and age on trace element levels in soft tissues. In this work, using inductively coupled plasma mass spectrometry, we studied the contents of 72 elements in soft tissues of M. galloprovincialis aged 0.5–4, which were sampled at three stations within a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…There exist special methods of multivariate analysis, such as linear discriminant analysis (LDA) and canonical analysis of principal coordinates (CAP), that are best suited for this purpose. These methods have been used for the accurate tracking of sampling locations of a number of molluscs [75,[123][124][125][126][127][128], and CAP proved to be superior, compared to LDA, in the correct classification of the locations [75]. In the present work, it is shown that mollusc species can also be successfully identified based on the REE contents in their shells.…”
Section: Multivariate Analysismentioning
confidence: 64%
See 4 more Smart Citations
“…There exist special methods of multivariate analysis, such as linear discriminant analysis (LDA) and canonical analysis of principal coordinates (CAP), that are best suited for this purpose. These methods have been used for the accurate tracking of sampling locations of a number of molluscs [75,[123][124][125][126][127][128], and CAP proved to be superior, compared to LDA, in the correct classification of the locations [75]. In the present work, it is shown that mollusc species can also be successfully identified based on the REE contents in their shells.…”
Section: Multivariate Analysismentioning
confidence: 64%
“…In CAP, species identity was the group factor, and the number of permutations in the hypothesis testing was 999. The fundamentals for both multivariate ordination techniques are briefly outlined in the Supplementary Materials to [75]. For the agglomerative hierarchical cluster analysis (CLUSTER function), no standardization was applied, and the unweighted pair-group average was chosen as the clustering algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations